KEDUDUKAN KOMISI PEMBERANTASAN KORUPSI (KPK) DALAM STRUKTUR KETATANEGARAAN INDONESIA DITINJAU DARI HUKUM ISLAM - Puspitasari, Yopa (Fakultas Syari'ah Institut Agama Islam Negeri (IAIN) Bengkulu, 2019)
Abstract: The position of the Corruption Eradication Commission is currently a problem, because its authority is too broad and even exceeds the institutions regulated in the constitution. The Corruption Eradication Commission, is an institution regulated in Law Number 30 of 2002 concerning the Corruption Eradication Commission. In Islamic law itself the institution of the Corruption Eradication Commission is not regulated in a special institution such as in Indonesia, but there is an institution that is almost the same as the Corruption Eradication Commission, namely the Al-Mazalim Region. This research is juridical normati with the primary source is the Law on the Eradication of Corruption Crime and Books relating to the Al-Mazalim Region. The results of the study show that the issue of the position of the Corruption Eradication Commission is regulated in Law No. 30 of 2002, where the Corruption Eradication Commission according to the Act is an independent institution free from the influence of any power. Although the institution of the Corruption Eradication Commission was not the main institution regulated by the 1945 Constitution but the Commission which was regulated by Law, but its position was the same as the institutions stipulated in the 1945 Constitution. `, and al-Hisbah region, namely resolving cases that cannot be resolved by the two judicial institutions, namely the problem of persecution carried out by the authorities, judges, or their families. In addition, the Al-Mazhalim Region is independent with no intervention by the Head of State or State Officials. Keywords: Corruption Eradication Commission; Independent; Al-Mazalim Region.